Desempenho de cadeias de suprimento no ambiente de negócios da era digital: um estudo dos elos da indústria de autopeças brasileira - Lucht, Richard Rigobert (2004)
The business environment is currently undergoing rapid and intense changes which are spurred by the emergence and strengthening of the global economy, the transformation of industrial economies and societies into knowledge-based service economies and by the emergence of the digital firm. These changes sharpen competition in all segments of society where, eventually, not all organizations will survive. It is amid this complex scene organizations are, continuously, looking for alternatives to face these changes. In this context, a major initiative involves supply chain management. After all, the odds that an organization will be successful are directly related to its competence in managing and participating in its supply chain. This fact implies that the business performance becomes strategic, when observed under the perspective of its performance as a supply chain's link. On other hand, it still exist an expressive lack of robust analytical models that can aid in evaluating supply chain performance and ranking the initiatives aimed at systemic improvements. The practical result is that several decisions are made based in the experience, intuition or faith, without structuring and modeling all their elements. The objective of this work is to identify the main technological and processes integration aspects, which impacts in the enterprise's performance, when one observes it as part of a supply chain. This research considers the particular case of the Brazilian Autoparts Industry as its investigation field, since this industry holds the potential for larger returns accruing from efficient supply chain management. The first main contribution of this thesis is the preposition of a theoretical model, which allows building a mathematical equation that measures business performance when observing the situation of the Brazilian Autoparts Industry's value chain. Finally, further studies can be carried out in other industries, including the services ones, using the proposed theoretical framework.